Alien earths : the new science of planet hunting in the cosmos - Kaltenegger, Lisa, 1977- (St. Martin's Press, 2024)
"Riveting and timely, a look at the research that is transforming our understanding of the cosmos in the quest to discover whether we are alone. For thousands of years, humans have wondered whether we're alone in the cosmos. Now, for the first time, we have the technology to investigate. But once you look for life elsewhere, you realize it is not so simple. How do you find it over cosmic distances? What actually is life? As founding director of Cornell University's Carl Sagan Institute, astrophysicist Lisa Kaltenegger has built a team of tenacious scientists from many disciplines to create a specialized toolkit to find life on faraway worlds. In Alien Earths, she demonstrates how we can use our homeworld as a Rosetta Stone, creatively analyzing Earth's history and its astonishing biosphere to inform this search. With infectious enthusiasm, she takes us on an eye-opening journey to the most unusual exoplanets that have shaken our worldview - planets covered in oceans of lava, lonely wanderers lost in space, and others with more than one sun in their sky! And the best contenders for Alien Earths. We also see the imagined worlds of science fiction and how close they come to reality. With the James Webb Space Telescope and Dr. Kaltenegger's pioneering work, she shows that we live in an incredible new epoch of exploration. As our witty and knowledgeable tour guide, Dr. Kaltenegger shows how we discover not merely new continents, like the explorers of old, but whole new worlds circling other stars and how we could spot life there. Worlds from where aliens may even be gazing back at us. What if we're not alone?"--